A Study of Financial Crimes in the Banking Sector of Bangladesh - Kabir, Musnun; Hosen, Md. Mosharaf (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
In recent years, Bangladesh has witnessed significant financial crimes within the banking sector, which pose a serious concern for the country. This research investigates the nature and contributing factors of financial crime in the banking sector, along with its primary causes and consequences. The study adopts a qualitative and descriptive approach to examine the modus operandi and impacts of such crimes. Secondary data have been collected from relevant literature, annual reports of Bangladesh Bank, and reviews of pertinent laws and legal cases. Additionally, this study explores various legal measures that can be implemented to curb financial crime in the banking sector. It also highlights the most critical actions that could be taken to prevent these crimes. The aim is for readers to gain a deeper understanding of financial crime and the mechanisms by which law enforcement addresses such offenses. The researcher has analyzed the nature, causes, effects, and potential preventive measures regarding financial crime in Bangladesh's banking sector.